Food for thought. Malnutrition risk associated with increased risk of healthcare-associated infection. Issue 3 (March 2019) - Fitzpatrick, F.; Skally, M.; O'Hanlon, C.; Foley, M.; Houlihan, J.; Gaughan, L.; Smith, O.; Moore, B.; Cunneen, S.; Sweeney, E.; Dinesh, B.; O'Connell, K.; et al.
Summary: Background: Infection and malnutrition are interconnected. UK and Irish guidelines recommend the Malnutrition Universal Screening Tool (MUST) for nutritional risk screening. Patients with a MUST score of ≥2 are considered at high risk of malnutrition and referral for nutritional assessment is recommended. Aim: To explore the association between healthcare-associated infection (HCAI) and the MUST score categories of patients. Methods: This was a cross-sectional study in May 2017 on ten representative wards in our institution. Patient demographics, MUST score, presence of medical devices, HCAI and antimicrobial use were collected. Findings: Of 240 patients, the HCAI prevalence was 10.4% ( N = 25) and 26% ( N = 63) were at high risk of malnutrition (MUST score ≥2). Patients with HCAI were more likely to have had surgery (odds ratio (OR): 5.5; confidence interval (CI): 2.1–14.3; P < 0.001), a central vascular catheter (OR: 10.0; CI: 3.6–27.2; P < 0.001), or a urinary catheter in situ (OR: 7.5; CI: 2.8–20.0; P < 0.001), and to have a high risk of malnutrition (OR: 4.3; CI: 1.7–11.2; P < 0.001). A higher MUST score remained a significant predictor of a patient having HCAI on multivariate regression analysis (CI: 0.2–0.6; P < 0.001). Conclusion: Patients at risk of malnutrition when assessed with the MUST were more likely to have HCAI. However, prospective studies are required to investigate the temporal association between MUST and HCAI and which interventions best address malnutrition risk and HCAI reduction in different settings.